If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2r + -4 + 3r = 2.5 Reorder the terms: -4 + 2r + 3r = 2.5 Combine like terms: 2r + 3r = 5r -4 + 5r = 2.5 Solving -4 + 5r = 2.5 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 5r = 2.5 + 4 Combine like terms: -4 + 4 = 0 0 + 5r = 2.5 + 4 5r = 2.5 + 4 Combine like terms: 2.5 + 4 = 6.5 5r = 6.5 Divide each side by '5'. r = 1.3 Simplifying r = 1.3
| 3c-4c+1+5c+2+3= | | 4-2(2x-2)=2(4-3x) | | 9+5x=-40 | | 1-12x+2x=3x+2 | | 2r-4+3r=25 | | 4(a+7)-2a=a-3 | | 22x-8(2x-3)=50 | | 30+x=31 | | 5y-5=7+4(y-4) | | 8-5(a+2)=-6a+9 | | 15y+3+7x=180 | | 3x-18=-6x | | 4x-23=12x+53 | | 4x^2+72+324=0 | | 5p-(3p+p)=6p+1 | | 12x-2(4x+-4)=-24 | | ?8c+21=2c+1 | | 3x-4=8x+10 | | x+6(4)=18 | | 6x-2x-6=5 | | G^2-20g+10=0 | | -75-k=-92 | | 15x^4-30x^2+15x=0 | | -27+15x=33-15 | | x+(3x-22)=180 | | A=4tg(2x+1)+3tg(3x-1) | | 11x+49=0 | | ln(3)=8 | | 2+3(t+4)=11 | | 5y-28=6x | | 4x+5=-8x-7 | | .04x+8=24 |